The first case series analysis on efficacy of esmolol injection for in-hospital cardiac arrest patients with refractory shockable rhythms in China - Rui Lian; Guochao Zhang; Shengtao Yan; Lichao Sun; Wen Gao; Jianping Yang; Guonan Li; Rihong Huang; Xiaojie Wang; Renyang Liu; Guangqing Cao; Yong Wang; et al. (Frontiers Media S.A., 2022)
Background: This study assessed the effects of esmolol injection in patients with in-hospital cardiac arrest (IHCA) with refractory ventricular fibrillation (VF)/pulseless ventricular tachycardia (pVT).Methods: From January 2018 to December 2021, 29 patients with IHCA with refractory shockable rhythm were retrospectively reviewed. Esmolol was administered after advanced cardiovascular life support (ACLS)-directed procedures, and outcomes were assessed.Results: Among the 29 cases, the rates of sustained return of spontaneous circulation (ROSC), 24-h ROSC, and 72-h ROSC were 79%, 62%, and 59%, respectively. Of those patients, 59% ultimately survived to discharge. Four patients with cardiac insufficiency died. The duration from CA to esmolol infusion was significantly shorter for patients in the survival group (SG) than for patients in the dead group (DG) (12 min, IQR: 8.5-19.5 vs. 23.5 min, IQR: 14.4-27 min; p = 0.013). Of those patients, 76% (22 of 29) started esmolol administration after the second dose of amiodarone. No significant difference was observed in the survival rate between this group and groups administered an esmolol bolus simultaneously or before the second dose of amiodarone (43% vs. 64%, p = 0.403). Of those patients, 31% (9 of 29) were administered an esmolol bolus for defibrillation attempts ≤ 5, while the remaining 69% of patients received an esmolol injection after the fifth defibrillation attempt. No significant differences were observed in the rates of ≥ 24-h ROSC (67% vs. 60%, p = 0.73), ≥ 72-h ROSC (67% vs. 55%, p = 0.56), and survival to hospital discharge (67% vs. 55%, p = 0.56) between the groups administered an esmolol bolus for defibrillation attempts ≤ 5 and defibrillation attempts > 5.Conclusion: IHCA patients with refractory shockable rhythms receiving esmolol bolus exhibited a high chance of sustained ROSC and survival to hospital discharge. Patients with end-stage heart failure tended to have attenuated benefits from beta-blockers. Further large-scale, prospective studies are necessary to determine the effects of esmolol in patients with IHCA with refractory shockable rhythms.